Long-term evolution of cartilage abnormalities and osteophytes in the fingers of elite sport climbers: a cross-sectional 10-year follow-up study - Pastor, T.; Schweizer, A.; Reissner, L.; Pastor, T.; Spörri, J.; Fröhlich, S. (European Journal of Sport Science, 2022)
The sequelae of high mechanical stress to the proximal interphalangeal (PIP) and distal interphalangeal (DIP) joints of the fingers in elite sport climbers and its contribution to the development of osteoarthritis are still relatively unknown. The purpose of this study was to investigate the evolution of cartilage abnormalities of the PIP and DIP joints, as well as the progress of osteophytes, in the fingers of elite sport climbers with a minimum of 25 years of climbing history over the time period of the last 10 years. Moreover, their actual cartilage abnormalities and osteophyte occurrence were compared to non-climbing age-matched controls. 31 elite male sport climbers and 15 male non-climbers underwent a sonographic examination of the PIP and DIP joint cartilage and osteophyte thickness in the frontal and sagittal plane of digits II to V of both hands. The same cohort had already been measured with an identical protocol ten years earlier (follow-up-rate of 100%). Compared to the baseline assessment 10 years earlier, the cartilage thickness of sport climbers has significantly decreased; however, it was still greater than in age-matched controls. Moreover, sport climbers showed significantly higher relative frequencies of osteophyte occurrence than non-climbers (all fingers and joints). Nevertheless, despite a substantial (and compared to baseline a further increased) occurrence of osteophytes in elite sport climbers, there was no association between the radiological signs of osteoarthritis and pain within the last 6 months prior the follow-up investigation.